The combined role of biomarkers and interim PET scan in prediction of treatment outcome in classical Hodgkin's lymphoma: a retrospective, European, multicentre cohort study. Issue 10 (October 2016) - Agostinelli, Claudio; Gallamini, Andrea; Stracqualursi, Luisa; Agati, Patrizia; Tripodo, Claudio; Fuligni, Fabio; Sista, Maria Teresa; Fanti, Stefano; Biggi, Alberto; Vitolo, Umberto; Rigacci, Luigi; Merli, Francesco; et al.
Summary: Background: Early-interim fluorodeoxyglucose (FDG)-PET scan after two ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine) chemotherapy courses (PET-2) represents the most effective predictor of treatment outcome in classical Hodgkin's lymphoma. We aimed to assess the predictive value of PET-2 combined with tissue biomarkers in neoplastic and microenvironmental cells for this disease. Methods: We enrolled 208 patients with classical Hodgkin's lymphoma and treated with ABVD (training set), from Jan 1, 2002, to Dec 31, 2009, and validated the results in a fully matched independent cohort of 102 patients with classical Hodgkin's lymphoma (validation set), enrolled from Jan 1, 2008, to Dec 31, 2012. The inclusion criteria for both the training and validation sets were: the availability of a representative formalin-fixed, paraffin-embedded tissue sample collected at diagnosis; treatment with ABVD with or without radiotherapy; baseline staging and interim restaging after two ABVD courses with FDG-PET; no treatment change based solely on interim PET result; and HIV-negative status. We used Cox multivariate analysis classification and regression tree (CART) to compare the predictive values of these markers with that of PET-2 and to assess the biomarkers' ability to correctly classify patients whose outcome was incorrectly predicted by PET-2. Findings: In multivariate analysis, PET-2 was the only factor able to predict both progression-free survival (hazard ratio [HR] 33·3 [95% CI 13·6–83·3]; p<0·0001) and overall survival (HR 31·3 [95% CI 3·7–58·9]; p=0·002). In the training set, no factor had a stronger adverse predictive value than a positive PET-2 scan and none was able to correctly reclassify PET-2 positive patients. In PET-2 negative patients, expression of CD68 (≥25%) and PD1 (diffuse or rosetting pattern) in microenvironmental cells, and STAT1 negativity in Hodgkin Reed Sternberg cells identified a subset of PET-2 negative patients with a 3 year progression-free survival significantly lower than that of the remaining PET-2 negative population (21 [64%] of 33 [95% CI 45·2–79·0] vs 130 [95%] of 137 [95% CI 89·4–97·7]; p<0·0001). These findings were reproduced in the validation set. Interpretation: The CART algorithm correctly predicted the response to treatment in more than a half of patients who had a relapse or disease progression despite a negative PET-2 scan, thus increasing the negative predictive value of PET-2. In keeping with preliminary results from interim PET response adapted clinical trials of patients with advanced Hodgkin's lymphoma, there might be a non-negligible proportion of treatment failures in the interim PET negative group treated with standard ABVD. Funding: Italian Association for Cancer Research, Bologna Association against leukaemia, lymphoma and myeloma, and Bologna University.